2003
DOI: 10.1046/j.1440-1630.2003.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Working in a community recreation program: A study of consumer‐staff perspectives

Abstract: Consumers working as service providers make unique contributions to the quality, accessibility, and responsiveness of mental health services. Relatively little research has explored these roles. This study used a naturalistic inquiry methodology to explore consumer-staff views of working in a program that assists people living with mental illness to access recreation. Three consumer-staff were interviewed about the rewards and challenges of their work. Qualitative analysis of participants' views identified eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Greater insight into others’ experiences put individual egos aside and led to an appreciation of what others had been through [ 3 , 8 , 13 , 19 , 25 ]. Close PSW teams were facilitated by their shared illness experience, shared programme goals and support of each other’s different positions in the recovery journey [ 3 , 4 , 12 , 15 , 22 ]. Connection with other PSWs was highly valued and allowed individuals to feel safe as themselves, integrating their psychiatric or physical condition into their life [ 1 , 3 , 4 , 8 , 22 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater insight into others’ experiences put individual egos aside and led to an appreciation of what others had been through [ 3 , 8 , 13 , 19 , 25 ]. Close PSW teams were facilitated by their shared illness experience, shared programme goals and support of each other’s different positions in the recovery journey [ 3 , 4 , 12 , 15 , 22 ]. Connection with other PSWs was highly valued and allowed individuals to feel safe as themselves, integrating their psychiatric or physical condition into their life [ 1 , 3 , 4 , 8 , 22 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of peer support models in healthcare is well established in mental health services where peer support workers (PSWs) serve to improve engagement with healthcare and positive health outcomes among their clients [ 1 15 ]. PSWs are usually recruited from the same client pool as the individuals that they are looking after, thus sharing similar experiences or characteristics with the target intervention group.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the ongoing disruptions experienced within their lives, each of the participants appeared to have found ways to manage their illness sufficiently to maintain their worker-role. The need to find ways to stay well, manage the levels of stress and control persistent symptoms to pursue and maintain employment has also been reported elsewhere (Honey, 2000;Nagle, Valiant Cook, & Polatajko, 2002;Yuen & Fossey, 2003). Hence, work environments with both structure and flexibility, which enable the person with a psychiatric disability to take control in managing the fatigue, persistent symptoms and stress, seem important.…”
Section: Ongoing Struggle With Illnessmentioning
confidence: 88%
“…The main concepts include the 'deinstitutionalisation' © 2007 Australian Association of Occupational Therapists of consumer care away from large psychiatric hospitals (Leff & Trieman, 2000;Yuen & Fossey, 2003); and a greater focus on alternative residential and community-based accommodation options for people with serious mental illness.…”
Section: The Development Of Community Residential Programsmentioning
confidence: 99%
“…A background paper on recovery by Queensland Health (2004) reported how people with mental illness must not just participate in service delivery planning and evaluation, but 'people must also be afforded the information and skills necessary to make their interaction with service providers genuine, relevant and effective' (Queensland Health, p. 13). Yuen and Fossey (2003) reported on consumers becoming increasingly involved in policy-making participation while © 2007 Australian Association of Occupational Therapists Van Wersch and Eccles (2001) described how consumers in northern England are involved in the development of clinical guidelines, and concluded that further research is needed to establish how this might be best achieved. In the Netherlands, Plochg and Klanzinga (2002) referred to levels of decision-making in healthcare service delivery, with patient empowerment being recognised as an area for quality improvement.…”
Section: Consumer and Carer Perspectives In Service Evaluationmentioning
confidence: 99%